Isolated fractures of the greater tuberosity in proximal humerus: does the direction of displacement influence functional outcome? An analysis of displacement in greater tuberosity fractures - Verdano, Michele Arcangelo; Aliani, Davide; Pellegrini, Andrea; Baudi, Paolo; Pedrazzi, Giuseppe; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: The treatment of isolated fractures of the greater tuberosity of the proximal humerus is still debated, especially in the case of minimally dispaced fractures. Differently from other proximal humerus fractures this kind of injury frequently affects young patients with high functional request. The aim of this study is to assess the outcome of patients treated conservatively for greater tubero-sity isolated fractures, comparing the clinical results in patients with different direction of fracture displacement. Methods: 38 patients with isolated fracture of greater tuberosity participated to the study and were evaluated at 17 months (10-26) of follow up using Constant Murley Score and DASH Score. Patients were divided in groups with different direction of displacement (10 no displacement, 13 postero-superior, 6 antero-superior and 9 antero-inferior displacement). Results: Patients with no displaced fractures had a mean Constant Murley Score of 82 and a mean DASH Score of 15; those with postero-superior displacement had a mean a Constant Murley Score of 61 and a mean DASH Score of 43; for antero-superior displacement the mean Constant Murley Score was 76 and the mean DASH Score of 18; for the antero-inferiorly displaced the mean Constant Murley Score was 83 and the DASH Score 16. Conclusion: Data suggest that postero-superior displacement leads to poorer outcomes than undisplaced or displaced in other directions fractures treated conservatively.